Development of arrayed colonic organoids for screening of secretagogues associated with enterotoxins - Gunasekara, Dulan B. (Anal Chem, 2018)
Enterotoxins increase intestinal fluid secretion through the modulation of ion channels as well as activating the enteric nervous and immune systems. Colonic organoids, also known as colonoids, are functionally and phenotypically similar to in vivo colonic epithelium, and have been used to study intestinal ion transport and subsequent water flux in physiology and disease models. In conventional cultures, organoids exist as spheroids embedded within a hydrogel patty of extracellular matrix, and form at multiple depths impairing efficient imaging which is necessary to capture data from statistically relevant sample sizes. To overcome these limitations, an analytical platform with colonic organoids localized to the planar surface of a hydrogel layer was developed. The arrays of densely-packed colonoids (140-μm average diameter, 4 colonoids/mm(2)) were generated in a 96-well plate enabling assay of the response of hundreds of organoids so that organoid subpopulations with distinct behaviors were identifiable. Organoid cell types, monolayer polarity, and growth was similar to those embedded in hydrogel. An automated imaging and analysis platform efficiently tracked over time swelling due to forskolin and cholera toxin stimulated fluid movement across the cell monolayer. The platform was used to screen compounds associated with the enteric nervous and immune systems for their effect on fluid movement across epithelial cells. Prostaglandin E2 promoted increased water flux in a subset of organoids resulting in organoid swelling confirming a role for this inflammatory mediator in diarrheal conditions but also illustrating organoid differences in response to an identical stimulus. By sampling a large number of organoids, the arrayed organoid platform permits identification of organoid subpopulations intermixed within a larger group of nonresponding organoids. This technique will enable automated, large-scale screening of the impact of drugs, toxins and other compounds on colonic physiology.